Isolated Superior Mesenteric Vein Tumor Thrombus in a Patient with Gastric Cancer - Barış Özcan; Metin Çevener; Ayşegül Kargı; Mustafa Özdoğan; Alihan Gürkan (Case Reports in Surgery)
Tumor thrombus in the portal vein can rarely originate from gastric cancer via hematogenous spread, with only few case reports published in the literature. Isolated superior mesenteric vein tumor thrombus in gastric cancer has not been previously reported. A 61-year-old male patient who had undergone distal gastrectomy and gastroenterostomy for gastric ulcer 20 years ago was diagnosed with an obstructive tumor originating from the gastroenterostomy anastomosis site on upper gastrointestinal endoscopy that was performed for complaints of fatigue, oral feeding problems, and anemia. The PET-CT imaging revealed a hypermetabolic mass in the gastroenterostomy region along with hypermetabolic suspected tumor thrombus in the superior mesenteric vein (SMV). A suspected tumor thrombus with contrast enhancement that completely obstructed the SMV was detected on triphasic abdominal computed tomography. Decision for surgery was made due to gastric tumor obstruction. Firstly, lesions suspected with tumor thrombus were extirpated from the SMV and sent to frozen section. Then, it was completely recanalized. A locally advanced tumor originating from the gastroenterostomy anastomosis site that totally obliterated the lumen was observed on surgical exploration. After proving tumor thrombus by frozen, near-total gastrectomy was performed for palliative purposes. Histopathologic examination of the specimen showed gastric invasive adenocarcinoma and tumor thrombi in the SMV (T4N2M1). The patient received adjuvant chemotherapy, and he is at his 22nd-month follow-up with extensive hepatic metastases and intra-abdominal disease. It should be kept in mind that gastric cancer may lead to portal vein tumor thrombus or that it may rarely be associated with an isolated SMV tumor thrombus, both of which are associated with poor prognosis.